SOCIALIZATION AND ASSISTANCE OF ON-BOARDING TRAINING TO INCREASE THE BRANDING OF FOSTERED MSMES BANK INDONESIA BALI PROVINCE - Suparna, Putu; Sumarno, Aditya Dewangga (LPPM Univ. Ibn Khaldun Bogor, 2024)
Service program activities through socialization and on-boarding training assistance to enhance the branding of MSMEs Fostered by Bank Indonesia Bali Province through the On Boarding Training program. The purpose of this socialization and mentoring is to analyze the effectiveness of the socialization and mentoring methods used, the level of understanding of Local MSME actors towards On Boarding, as well as its impact on the adoption of branding with digital assistance among MSME actors and the general public in Bali. Using the method of socialization and mentoring with interviews with MSME actors and the community that On Boarding training can improve Branding and be able to reach the desired target market, this socialization involves participants, MSME actors, the community and representatives of Bank Indonesia. The results of this socialization and mentoring show that the On Bording Training program has succeeded in improving the branding and understanding of MSME actors about On Boarding, and encouraging an increase in the use of digitally assisted branding in various local MSME sectors. This article also identifies challenges in the implementation of On Boarding Training and provides recommendations for future improvement of the socialization program.